Evaluation and Analysis of Uncertainty Measurement of The Sound Level Meter Calibration by Coupler Method - Bondan Dwisetyo; Denny Hermawanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2021)
The evaluation and analysis of uncertainty measurement of sound level meter calibration by coupler method was carried out by Research Group for Acoustics and Vibration – National Standardization Agency of Indonesia (BSN). The aims of this work is to evaluate and analyze the uncertainty measurement of sound level meter (SLM) calibration using the coupler method, where it is focused for A-frequency weighting as main parameter based on Guide to the expressions of Uncertainty in Measurement (GUM). The uncertainty budgets that obtained of this work consists of a repeated measurement of sound level meter test using the multifunction acoustic calibrator as the reference instrument, readability of SLM, sound pressure level calibration of the reference along with drift of the standard, sound pressure response, the level of accuracy, the total harmonic distortion with noise, and the capability of the used insulation box to insulate background noise from outside. From the result of case study, the standard instrument withal its sound pressure response and level of accuracy has the highest contribution to provide the significant evaluation of the expanded uncertainty at the frequency of 8000 Hz that put of the values are 0,17 dB and 0,14 dB respectively. After that, the obtained expanded uncertainty reach up to 0,48 dB of this frequency. In addition, this result also state that the proposed expanded uncertainty values are below to the maximum of acceptance values that required by IEC 61672-1:2013. Thus, it is acceptable and is considered to be applicated further for the calibration of sound level meter, and other the utilized microphone instruments.